2022
DOI: 10.3389/fcvm.2022.874087
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact and Prognostic Role of Triglyceride to High-Density Lipoprotein Cholesterol Ratio in Patients With Chronic Coronary Syndromes at Very High Risk: Insights From the START Study

Abstract: BackgroundSeveral studies have reported that the combination of high TG and low HDL-C, as simplified by the TG/HDL-C ratio, was a predictor of cardiovascular disease independent of LDL-C level. Nevertheless, poor data are available on the predictive role of TG/HDL-C ratio in very high risk (VHR) patients with chronic coronary syndromes (CCS).MethodsUsing the data from the STable Coronary Artery Diseases RegisTry (START) study, an Italian nationwide registry, we assessed the association between the TG/HDL-C rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Comparable results were reported for TG/HDL-C, which predicts worse outcomes in patients with acute coronary syndrome and ischemic stroke [54][55][56][57][58][59][60], with wide heterogeneity in its predictive value across different ethnicities [48]. Data regarding the relationship between LAP and VAI showed a significant association with both the short-and long-term risk of CVEs in nonobese patients [49][50][51].…”
Section: Discussionmentioning
confidence: 97%
“…Comparable results were reported for TG/HDL-C, which predicts worse outcomes in patients with acute coronary syndrome and ischemic stroke [54][55][56][57][58][59][60], with wide heterogeneity in its predictive value across different ethnicities [48]. Data regarding the relationship between LAP and VAI showed a significant association with both the short-and long-term risk of CVEs in nonobese patients [49][50][51].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, overlay view and citations bursts detection are two of the central methods for tracing the evolution of science ( Yuan et al, 2021 ). The treatment of cardio-cerebrovascular diseases caused by AS is a major global health concern ( De Luca et al, 2022 ), and the application of molecular imaging will have a profound impact on the early diagnosis and precise treatment of AS ( Lin et al, 2021 ; Wang et al, 2021 ). Figure 7A shows that the research was divided into five clusters which constructed the knowledge structures in this field: (1) Nanoparticle-related studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that not only the index blood lipid level, but also their variabilities and controlling levels after discharge are of great significance to the secondary prevention and long-term prognosis of cardiovascular disease (2)(3)(4)(5). In addition to low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglyceride, several novel lipoprotein ratios have been proved with greater predictive power in cardiovascular prevention, especially the LDL-C to HDL-C ratio (LHR), which could reflect not only the atherogenic lipoprotein, but also the protective lipoprotein and their balance (6)(7)(8)(9). Jesús Millán et al pointed out that LHR was more predictive of cardiovascular disease risk than either lipoprotein alone (9).…”
Section: Introductionmentioning
confidence: 99%